Genetic analysis of agronomic traits in Gobhi Sarson (Brassica napus L) breeding lines - Ravindra Kumar; Meenakshi Sharma; Vijay Singh; Saurabh Gupta (Journal of Oilseed Brassica, 2026)
Understanding the knowledge of gene action and the nature of genes/ traits is important for an effective breedingprogram. The objective of this study was to determine the general combining ability (GCA) and specific combiningability (SCA), variances and their effects on seed yield and components of Gobhi Sarson (Brassica napus L.) breedingmaterials. Five diverse B. napus genotypes selected for their seed yield were crossed using a half-dialle mating design.The analysis of the variance of parents and their cross effects was significant for all parameters measured. Among fiveparents, two parents namely EC-338978 and RBS bold showed positive GCA effect may be considered as good generalcombiners for seed yield and components. The best four selected crosses with significant SCA effects for seed yield wereEC 338978 × RBS Bold, EC 338978 × HMS4, EC 338978 × BMS4 and RBS Bold × BMS4, respectively. The selectedcrosses are valuable genetic resources for B. napus breeding for seed yield and yield components in the Punjab region orsimilar environments.